2017
DOI: 10.1038/s41467-017-00834-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of celastrol to mesangial cells is effective against mesangioproliferative glomerulonephritis

Abstract: Mesangial cells-mediated glomerulonephritis is a frequent cause of end-stage renal disease. Here, we show that celastrol is effective in treating both reversible and irreversible mesangioproliferative glomerulonephritis in rat models, but find that its off-target distributions cause severe systemic toxicity. We thus target celastrol to mesangial cells using albumin nanoparticles. Celastrol-albumin nanoparticles crosses fenestrated endothelium and accumulates in mesangial cells, alleviating proteinuria, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 54 publications
6
119
0
Order By: Relevance
“…Similar to previous reported poor solubility and pharmacokinetics of celastrol [24], pristimerin in solution did not induce significant tumor growth inhibition in our preliminary study in PDX mouse model of endometrial cancer (data not shown). We therefore used a nanoparticle-based delivery approach to improve the pharmacokinetics and therapeutic efficacy of pristimerin.…”
Section: Quantification and Characterization Of Pristimerin-loaded Plsupporting
confidence: 90%
“…Similar to previous reported poor solubility and pharmacokinetics of celastrol [24], pristimerin in solution did not induce significant tumor growth inhibition in our preliminary study in PDX mouse model of endometrial cancer (data not shown). We therefore used a nanoparticle-based delivery approach to improve the pharmacokinetics and therapeutic efficacy of pristimerin.…”
Section: Quantification and Characterization Of Pristimerin-loaded Plsupporting
confidence: 90%
“…Celastrol is a triterpene compound obtained from the roots of the Tripterygium Wilfordi (thunder god vine) (17). Celastrol represented a promising treatment option for mesangioproliferative glomerulonephritis and other glomerular diseases (26). Celastrol improved obesity and metabolic dysfunction via the activation of heat shock factor 1-peroxisome proliferatoractivated ␥ coactivator-1␣ axis in mice (27).…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, a type of albumin nanoparticle with defined sizes of ~95 nm to deliver celastrol selectively to mesangial cells has been recently reported. 35 Hence, as shown in the real-time biodistribution in DN model mice, controlling particle size is an effective approach to realize renal target delivery. However, accumulation in peritubular capillaries does not seem to correlate with the size of nanoparticles, showing conspicuous accumulation characteristics in different portions of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…34 Most other kidney therapy studies based on size demonstrated that the accumulation of nanoparticles is restricted to the glomerular mesangium and the kidney's extracellular matrix, reaching the maximal glomerular deposition by using ~80 nm nanoparticles. 31,35 In addition, charge selectivity is also an important criterion for kidney targeting. Nanoparticles with a surface charge of ,15 mV have minimal macrophage uptake and long circulation time.…”
Section: Introductionmentioning
confidence: 99%